2004
DOI: 10.1039/b313832a
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide-stable ionic liquids: new and efficient media for electrosynthesis of functional siloxanes

Abstract: The electrogeneration of diorganylsilanones from difunctional precursors Y(CH(2))(3)(Me)SiX(2) and Ph(2)SiX(2)(Y = NH(2), CF(3), CN; X = Cl, OEt, OMe), performed in the presence of hexamethyldisiloxane or hexamethylcyclotrisiloxane (D(3)) in the ionic liquids [C(5)H(5)NC(8)F(18)].NTf(2), [C(5)H(5)NC(18)H(38)].NTf(2) and Me(3)BuN.NTf(2), which reveal high solubility of oxygen and are inert toward superoxide anion, allows functionalized siloxanes to be produced selectively in good isolated yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 20 publications
(3 reference statements)
2
24
0
1
Order By: Relevance
“…Very small quantity of potassium superoxide (KO 2 ) was added to the IL until its pH became 7. This is in agreement with Martiz et al [43], where they showed only after the grafting of pyridinium based IL with aliphatic perfluorinated chain, [C 5 H 5 N + C 8 The presence of the reverse peak (oxidation peak) confirms that the generated superoxide is stable in these ILs within the time limit of the experiment. The negligible background CV in the presence of nitrogen indicates that the IL is electrochemically stable in this range of potential.…”
Section: Reduction Of Dioxygensupporting
confidence: 90%
“…Very small quantity of potassium superoxide (KO 2 ) was added to the IL until its pH became 7. This is in agreement with Martiz et al [43], where they showed only after the grafting of pyridinium based IL with aliphatic perfluorinated chain, [C 5 H 5 N + C 8 The presence of the reverse peak (oxidation peak) confirms that the generated superoxide is stable in these ILs within the time limit of the experiment. The negligible background CV in the presence of nitrogen indicates that the IL is electrochemically stable in this range of potential.…”
Section: Reduction Of Dioxygensupporting
confidence: 90%
“…Shreeve and co-workers have contributed greatly in developing ILs based exotic cations. In addition, we saw also increased interests in chiral [66 -70] , sulfonium [71] , quaternary ammonium [72,73] and phosphonium IL [74][75][76] (see Fig. 2).…”
Section: Functionalization Of Ionic Liquidsmentioning
confidence: 86%
“…Indeed, ionic liquids exhibit rich physicochemical properties (i.e., hydrogenbonding ability, p-p interactions, ion pair-like solvation effect due to their pure ionic nature, Lewis/Brønsted acidity/basicity) that are likely to affect the chemical reactivity, especially in the case of charged reactants [6][7][8][19][20][21][22]. Thus, while a number of recent works have highlighted the advantages of conducting electrochemical analyses in RTILs by contrasting the results to those obtained in classical electrolytes [6,[12][13][14][15][16][17], little has been focused on the kinetics of electrochemical processes in these complex media. It is becoming apparent that the nature of ionic liquids does influence the heterogeneous electron-transfer processes [23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 98%
“…Although they were originally developed as versatile electrolytes in electrochemical devices [9][10][11], applications of RTILs as reaction media in electrochemistry are currently in widespread use [5,6]. They present particular and interesting prospects in electrochemical organic synthesis because they can be used as electrolyte without the need of adding any extraneous supporting salts [12][13][14][15][16][17]. This intrinsic property renders them a superior reaction media for preparative-scale electrosynthesis as compared with conventional electrolytes for which product recovery and solvent recycle are not very easy [18].…”
Section: Introductionmentioning
confidence: 98%